Surgical excision versus observation as initial management of desmoid tumors: A population based study. Issue 4 (April 2019) - Turner, Benjamin; Alghamdi, Mohamed; Henning, Jan-Willem; Kurien, Elizabeth; Morris, Don; Bouchard-Fortier, Antoine; Schiller, Daniel; Puloski, Shannon; Monument, Michael; Itani, Doha; Mack, Lloyd A.
Abstract: Synopsis: Desmoid tumors can be safely managed with watchful waiting, including either observation alone or tamoxifen/NSAIDs. Surgery at first presentation can be associated with significant treatment burden. Background: Immediate surgery was historically recommended for desmoid tumors. Recently, watchful waiting, (tamoxifen/NSAIDs or observation alone), has been advocated. Methods: All diagnoses of desmoid tumor within the Alberta Cancer Registry from August 2004 to September 2015 were identified. Patients with FAP were excluded. Demographics, tumor characteristics and treatment and outcome data were collected. Outcomes were compared between immediate surgery and watchful waiting. The effect of abdominal wall site on progression and recurrence and the effect of microscopic margin on recurrence were assessed with Fisher's exact test. Results: We identified 111 non-FAP patients. Median follow-up was 35 months from diagnosis. 74% were female. Mean age was 42. Fifty (45%) underwent watchful waiting, of whom 21(42%) progressed, with median PFS of 10 months. Fifty-three (48%) underwent resection at presentation, of whom 8 (15%) recurred, with median disease-free survival of 22 months. Abdominal wall lesions were equally represented in both groups, and equally likely to progress on watchful waiting (50% vs 39%, p = 0.53), but there was a trend toward decreased recurrence after surgery. (5% vs 23%, p = 0.08). Microscopic margin had no effect on recurrence (14% of margin negative vs 20% of margin positive, p = 1.0). Conclusions: Watchful waiting was successful in 58% of patients, and a further 28% only required one aggressive treatment thereafter, for a total of 86%. Surgery had a favorable recurrence rate (15%), but some recurrences were associated with significant treatment burden. Treatment should be tailored to individual patients in a multidisciplinary setting. A trial of observation appears warranted in most patients. Recurrence rate was not affected by positive margins.